TWO-DIMENSIONAL FLOW PATTERN MODEL IN THE WATERS OF BAKAU BAY BINTAN DISTRICT - Fahrianti, Anggun Safutri; Ma’mun, Asep; Febrianto, Try; Suhana, Mario Putra; Ritonga, Abdul Rahman (Politeknik Kelautan dan Perikanan Dumai, 2024)
Ocean currents are the movement of sea water masses in a certain direction caused by several factors, namely wind, tides and bathymetry. Hydrodynamic modeling aims to determine the speed and direction of ocean currents in the waters of Bakau Bay through a two-dimensional model. The current pattern of the north season to the east season is influenced by sea water masses with an average current speed ranging from 0.22-0.24 m/s, while the south season to West season currents with an average speed of 0.04-0.26 m/s, this shows the meeting of different water masses so that the speed and direction of the current results in random or rotating currents. From the calculations of the normality test and anova test, it is known that the field current and model simulation values are normally distributed and there is no significant difference in values in the two data, so based on the RMSE value, it shows that the difference in values between the model simulation results and direct data measurements is relatively small. This also shows that the ocean surface current model created is sufficient to describe actual conditions.